Influencing factors of red blood cell transfusion volume for premature neonatal pneumonia and its predictive value for feeding intolerance - Lili WANG; Jianrong WANG (Zhongguo shuxue zazhi, 2023)
Objective To investigate the influencing factors of red blood cell transfusion volume for premature neonatal pneumonia and its predictive value for feeding intolerance. Methods 272 infants of premature neonatal pneumonia treated with red blood cell transfusion were collected as the research objects. Red blood cell transfusion volume was investigated and its influencing factors were analyzed by multiple linear regression. Receiver operating curve (ROC) was used to analyze the predictive value of red blood cell transfusion volume on feeding intolerance in infants with premature neonatal pneumonia. Results The average red blood cell transfusion volume in infants with premature neonatal pneumonia was (76.19±26.03) mL. Multiple linear regression analysis showed that gestational age, birth weight, volume of blood collection and hemoglobin level before blood transfusion were influencing factors of red blood cell transfusion volume in infants with premature neonatal pneumonia (B=-1.930, -6.215, 1.041, -0.249, P<0.05). The incidence of feeding intolerance in infants with premature neonatal pneumonia was 19.5%. The transfusion volume of feeding intolerance group was significantly higher than that of the non-feeding intolerance group(P<0.05). ROC analysis showed that the area under curve (AUC) of red blood cell transfusion volume for predicting feeding intolerance was 0.755. Conclusion Gestational age, birth weight, volume of blood collection and hemoglobin level before blood transfusion are influencing factors of red blood cell transfusion volume in infants with premature neonatal pneumonia. The incidence of feeding intolerance in premature neonatal pneumonia is high. The red blood cell infusion volume is of good predictive value for the occurrence of feeding intolerance. Latrogenic blood loss and red blood cell transfusion volume should be minimized clinically.